Percepção do uso e atividade desinfetante de libidibia ferrea - Holanda, Jamile Rodrigues Cosme de (Universidade Federal Rural do Semi-Árido, 2019)
The population lives exposed to a diversity of microorganisms that are present in the environment with which they coexist daily. These microorganisms may be pathogenic or not. In order to control these microorganisms on the surfaces, disinfection with chemicals is currently carried out. These, in turn, have been causing health and environmental damage, as well as the development of resistance of these microorganisms. In this way, the need arises for the use of natural alternative measures. Since Libidibia ferrea is a tree with great medicinal potential, it is sought to analyze the inhibitory properties of L. ferrea leaves and decoct, and the phytochemical components, as well as the communities' knowledge and acceptance of this alternative disinfectant. effectiveness as a disinfectant. For this, the following methodologies were used: disc diffusion technique and growth curve under the action of juca to evaluate the antimicrobial activity; disinfectant evaluation test on plastic surfaces, stainless steel and ceramics and phytochemical prospecting, as well as the application of the product acceptability test and the questionnaire to evaluate the knowledge about the use of jucá in the rural communities of the municipality of Mossoró / RN. A statistical analysis was given by the SigmaPlot program, by One-Way ANOVA and One-Way ANOVA RM followed by Tukey, Kruskal-Wallis and Friedman. For the sensorial analysis the Wilconxon was used, being the values of 0,05 signified. As a result, in the well diffusion technique the sensitivity of S. aureus and E. feacalis to the decoction and for the extract P. aeruginosa, Micrococcus spp., Corynebacterium spp., S. Typhirium, S. aureus and E. feacalis . As for the growth curve evaluated after 24 hours, this showed a reduction of the absorbance value for the extract to P. aeruginoa, Corynebacterium spp., S. Typhirium and E. feacalis, being that for the decoction only the latter. In the test of the disinfectant action on the surfaces it was verified that there was a bacterial reduction for the decoction as for the extract considering the negative control in all the surfaces, except for S. Typhimurium in relation to the steel. Phytochemistry showed the presence of flavonoids, saponins, tannins, coumarins, steroids and phenolic compounds. It was also observed that in all the questionnaires evaluated there is a greater acceptance of disinfectant based on L. ferrea leaves. In this way it can be affirmed that the jucá-based disinfectant is an effective natural alternative and well accepted by the population
Keywords: Desinfecção; Extrato vegetais; Teste de sensibilidade microbiana; Análise sensorial; Decocto; Disinfection; Plant Extract; Microbial Sensitivity Test; Sensory Analysis; Decoct; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE